Finding Fitting Solutions to Assessment of Indigenous Young Children’s Learning and Development: Do It in a Good Way - Ball, Jessica (Frontiers in Education, 2021)
Standardized, norm-referenced assessments of young children’s learning and development pose a number of challenges when used with Indigenous children, beginning with the very notion of the construct “early childhood” that runs counter to some Indigenous ways of knowing and being. Indigenous community leaders and knowledge keepers reject the idea that all children should develop according to a homogenizing universal standard that is not grounded in specific culturally based goals and practices surrounding children’s development and does not respect each child’s unique character. Three key problems arise with creating appropriate assessment of Indigenous young children’s learning and development: (1) professional education programs have yet to decolonize and therefore typically transmit Euro-Western ways of knowing, goals for children’s development, norms, technologies, and tools to early childhood practitioners and clinical specialists; (2) school systems, early childhood programs, and practitioners face a barrage of pressure to measure children’s “progress” against universalist norms; and (3) knowledge of diverse Indigenous young children’s varied lived experiences in today’s urban and rural communities is extremely limited. This paper draws from the author’s many years of research with Indigenous children, families, and communities to cocreate culturally relevant assessment and to do it in a good way.